Unveiling the Chemical Composition, Enantiomeric Profile, Antibacterial, Anticholinesterase and Antioxidant Activity of the Essential Oil of Aloysia triphylla Royle - Cinthia Mejia-Ramos; Julio Reynaldo Ruiz-Quiroz; Maria Elena Salazar-Salvatierra; James Calva; Eddie Loyola-Gonzales; Haydee Chávez; Javier Hernán Chavez-Espinoza; Josefa Bertha Pari-Olarte; José Santiago Almeida-Galindo; Oscar Herrera-Calderon (Molecules, 2025)
Aloysia triphylla is widely used in traditional medicine from Peru for its sedative, digestive and anti-inflammatory properties. However, comprehensive studies on the biological activities of its essential oil (EO), particularly from Peruvian sources, remain limited. This study aimed to analyze the chemical composition and enantiomeric profile of A. triphylla EO and evaluate its antibacterial, antioxidant, anticholinesterase, and cytotoxic activities. The EO was obtained by steam distillation and analyzed using gas chromatography–mass spectrometry (GC-MS). A total of 62 compounds were identified, with (E)-caryophyllene (16.80%), β-pinene (9.96%), and germacrene D (10.00%) being the major components. Enantiomeric analysis revealed specific chiral signatures, including (−)-α-pinene, (+)-limonene, and (R)-(−)-linalool. The EO exhibited significant antibacterial activity, particularly against Bacillus subtilis (MIC = 5 µg/mL), and weak antioxidant activity (IC50 = 7720 and 4648 µg/mL for DPPH and ABTS, respectively). Additionally, the EO demonstrated moderate acetylcholinesterase inhibition (IC50 = 87.8 µg/mL) and cytotoxicity in the Artemia salina assay (LC50 = 964 µg/mL). These findings suggest that A. triphylla EO possesses promising bioactivities with potential applications in pharmaceutical and cosmetic fields.